Biogeochemical characteristics and fluxes of suspended particulate organic matter in response to low‐tide rainfall. (5th December 2017) - Chen, Si; Torres, Raymond
Abstract: We evaluated the effects of low‐tide rainfall on salt marsh particulate organic carbon (POC) cycling. Suspended sediment samples from intertidal creeks were collected during rain and no‐rain conditions. Bulk (carbon, nitrogen) and molecular (e.g., lignin) compositions of organic constituents in particulates were analyzed. Temporal patterns of suspended sediment concentration mimic fluctuations in rainfall intensity, but all POC constituents do not necessarily follow these patterns. For example, particulate organic matter concentrations in water column covaried with rain intensity yet organic matter (OM) contents in the particles showed trivial correlations with rain. In general, rainfall effects raised the suspended sediment and organic constituent concentrations in the water column by up to three orders of magnitude. Multivariate statistical analysis revealed that the rainfall‐entrained particulates were compositionally distinct from calm weather suspended particulates, from salt marsh surface sediment, and from creek bank surface sediment. Rainfall‐entrained particulates are depleted in bulk organic carbon and phytoplankton‐derived OM but enriched in lignin phenols. These observations indicate that rainfall‐runoff processes preferentially mobilize POC derived from Spartina alterniflora from marsh platforms and effectively transport these materials to intertidal creeks following low‐tide rainfall events. Moreover, average net transport rates by rainfall are 0.020 ± 0.002 gPOC m −2 mmRain −1, and this POC turnover rate amounts to ∼ 19% of the annual POC export from estuary to ocean. Therefore, estuarine outwelling estimates typically made under calm weather conditions represent minimum levels of POC export. Hence, low‐tide rainfall can be expected to substantially enhance the delivery of marsh‐derived POC to the coastal ocean.